The Association of Adipokines and Myokines in the Blood of Obese Children and Adolescents with Lipoprotein Lipase rs328 Gene Variants - Alexander V. Shestopalov; Vadim V. Davydov; Genrik T. Tumanyan; Elena D. Teplyakova; Tatiana P. Shkurat; Elena V. Mashkina; Mikhail A. Shkurat; Andrey M. Gaponov; Anastasia A. Sadova; Olga V. Borisenko; Sergey A. Roumiantsev (Journal of Obesity)
Obesity develops largely due to genetic factors, with the genetic polymorphism of lipid metabolism enzymes being of particular importance. However, it is still unclear how the genetic variants of one of the key enzymes in lipid transport, lipoprotein lipase (LPL), are associated with the endocrine function of mesenchymal tissues in obesity. The current study was aimed at the investigation of the LPL rs328 gene variant association with adipokines and myokines levels, as well as lipid metabolism indices in the blood of children and adolescents of both genders with obesity. We found that LPL polymorphism rs328 is not characterized by the differences in the levels of hormones, adipokines, and myokines and in the blood of healthy children and adolescents; however, it significantly affects these indices during obesity in gender-dependent manner. The shifts in hormones, adipokines, and myokines manifest mostly in the obese individuals with Ser447Ser genotype rather than with 447Ter genotype. Obese boys homozygous for Ser447Ser have more elevated leptin levels than girls. They also demonstrate lower adiponectin, apelin, prolactin, and osteocrine levels than those in obese girls with the same genotype. The gender-based differences are less pronounced in individuals with 447Ter genotype than in the homozygotes for 447Ser. Thus, we conclude that the polymorphism rs328 of the lipoprotein lipase gene is accompanied by the changes in hormones, adipokines, and myokines levels in the blood of children and adolescents with obesity in gender-dependent manner.